PENGELOLAAN DANA DESA: Studi kasus di Desa Gondangrejo Kecamatan Wonorejo Kabupaten Karanganyar - Wenda, Girinius (JI@P, 2017)
Girinius Wenda, 2017. âThe Management of the Viilage Fund in thePerspective of Regent Regulation of Karanganyar Number 93, 2015Dealing with Instruction on Using the Technical Village Fundâ.(Case Study of the Management of the Village Fund in Wonorejo VillageGondangrejo Subdistrict Karanganyar Regency). Graduate Program ofPublic Administration Slamet Riyadi University, Thesis, unpublished.This study aimed to analyze the management of funds of the village in thevillage of Wonorejo, Gondangrejo Subdistrict, Karanganyar Regency. Thisresearch intends to identify factors supporting and restricting fundmanagement in perspective of the Regent Regulation of Karanganyarnumber 93 year 2015 dealing with the use of the village fund. This researchemployed descriptive qualitative method. Primary as well as secondarydata related to the situation and empirical condotion concerning to villagefund management were collected. Research result showed that theimplementation of village fund in the perspective of Karanganyar Regentregulation number 93 year 2015 in Wonorejo Village ran pretty smothly inimplementing some management functions. However, on the other hand,with regard to village community participation in providing suggestions andcriticisms in the village development discussion on development planningstill felt lacking. This fact was proved by the changings of the amount offunds and of physical infrastructures in the some local areas (dusun). Thiswas caused by urgency and by the benefits of the project for the localpeople.Key words: management; planning; implementation; participation..